2023
DOI: 10.1001/jamanetworkopen.2023.3398
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Association Between Alcoholic Beverage Type and Serum Urate Levels Using Standardized Ethanol Content

Abstract: ImportanceDifferences have been observed in the association of serum urate levels with consumption of different types of alcoholic beverages. However, previous studies have not standardized the unit of intake for ethanol content, and only limited types of alcoholic beverages have been evaluated.ObjectiveTo examine differences in the association of serum urate levels with various types of alcoholic beverages when their intakes are standardized for ethanol content.Design, Setting, and ParticipantsThis retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 47 publications
2
4
0
Order By: Relevance
“…This differs from other studies which found no significant difference between sexes [ 2 , 20 ] or significant effects in males but an absence of effect among females [ 21 , 22 ]. Consistent with previous studies, beer intake was associated with the largest increase in serum urate level and gout, followed by spirits [ 2 4 , 20 , 23 , 24 ]. While moderate wine intake did not associate with serum urate or gout in several earlier studies [ 2 4 , 20 ], we demonstrated significant association of wine consumption with increased serum urate level among all groups and with gout among men.…”
Section: Discussionsupporting
confidence: 91%
“…This differs from other studies which found no significant difference between sexes [ 2 , 20 ] or significant effects in males but an absence of effect among females [ 21 , 22 ]. Consistent with previous studies, beer intake was associated with the largest increase in serum urate level and gout, followed by spirits [ 2 4 , 20 , 23 , 24 ]. While moderate wine intake did not associate with serum urate or gout in several earlier studies [ 2 4 , 20 ], we demonstrated significant association of wine consumption with increased serum urate level among all groups and with gout among men.…”
Section: Discussionsupporting
confidence: 91%
“…Various factors contributed to the extent of the association between alcohol change and SU change. As with previous studies,10 11 13–15 beer intake was most strongly associated with SU level changes in this study. Beer includes more purine bodies compared with other alcohols 32.…”
Section: Discussionsupporting
confidence: 89%
“…Previous cross-sectional studies have demonstrated the associations of alcohol intake with SU level 10–16. The association between one daily beer intake and SU varied depending on studies but ranged up to 0.5 mg/dL (online supplemental table 4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations